DECONSTRUCTION THE CONCEPT OF GUARDIAN IN TRADITION SUFISM: BETWEEN LEGEND, HISTORY, AND SOCIAL REALITY - Kurniawan, Satunggale (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2025)
This study explores the deconstruction of the concept of wali (saint) in Sufi tradition, focusing on its transformation from a purely spiritual notion into a multidimensional social and cultural construct. Using a qualitative-critical approach and discourse analysis, this research examines classical Sufi texts, contemporary scholarship, and social representations of wali in digital media. The findings reveal that in classical Sufism, wali is understood as a servant of God who achieves closeness through spiritual purification and divine love. However, when intertwined with local culture, the concept evolves into a mythologized and institutionalized figure embodying spiritual authority and social power. In modern contexts, the image of wali is further mediated through digital platforms, often resulting in sensationalized and commodified portrayals detached from authentic Sufi values. The study argues that deconstructing the wali discourse is essential to rediscover its ethical and spiritual essence while exposing ideological and cultural distortions. Ultimately, this research highlights that wali remains relevant as a moral and social guide, provided the concept is reinterpreted critically and contextually in light of contemporary religious and social realities